Efficiency of the use of mobile games in water at the stages of primary teaching for children of primary school age - Шейко, Лилия; Пащенко, Наталия (Slobozhanskyi Herald of Science and Sport, 2018)
Liliya Sheyko & Nataliia Pashchenko The article offers the results of the study of the effectiveness of various programs for teaching the swimming of children of primary school age with the use of mobile games in water. Purpose: to establish the effectiveness of various methodological approaches in the education of children of primary school age in the process of physical preparedness and swimming. Materials & Methods: analysis and generalization of the data of scientific and methodological information, analysis of the methods of teaching the swimming of children of primary school age and organization of lessons in the health groups of the basins of Kharkov, pedagogical observation, experiment, mathematical statistics. Results: it was established that physical culture and health-improving swimming classes for children of primary school age in accordance with the training programs in the EG and CG groups contributed to mastering the swimming skill and mastering the technique of sporting methods of crawl on the chest and back. In the process of comparative pedagogical experiment it was proved that swimming by the program, providing for the use of specially selected outdoor games in water during the main part of each of 36 classes, contributed to more expressed intra-group growth of the majority of indicators of swimming preparedness in comparison with the lessons in the program, where the games were allocated only 35% of the time. Conclusions: іt is determined that the application of the program with extensive use of games in the main part of the lesson makes the classes more interesting, emotional and enables children to get rid of their uncertainty in their abilities.